Serviço social: cotidiano e produção de conhecimento em Angola - Isidro, Eduardo Carlos (2019)
This work, whose theme is “Social Service: Everyday and Knowledge Production in Angola” was held in Angola, where colonization equalized and stagnated life, where the burden of war from 1961 to 2002, and its vestiges, we present here. These are pointed out as causing the misery that the populations experience today. But we believe they are consequences of partial understanding about social being. The method of apprehending reality and its use in the organization of nations and institutions can create excluded in the productive process and consumption of goods and services. Our work explores and identifies the possibiliza that the Social Service has for the production of knowledge capable of changing the social conditions in which the country is currently. The work was produced around the critical-historical theory, assuming the production of knowledge as inseparable from professional work. We analyzed 30 Social Worker testimonials in their occupational spaces in 6 provinces of Angola, formed before and after 1975. We analyzed 10% of the TCC’s and reports of internships in the last year of graduation (2010 to 2017), of the two training institutes in a country of 25 million inhabitants. We prefer to preserve the originality of the information collected so that it serves as an analysis of other views. There are possibilities for the work and production of transformative knowledge in Angolan daily life, because neither the authors in the analyzed documents nor their speeches in the occupational spaces agree with the direction that the country and the profession have taken